Collaborative learning and social media acceptance for student engagement / Teo Siew Chein, San Zheng Jie and Koo Ah Choo - Teo, Siew Chein; San, Zheng Jie; Koo, Ah Choo (Faculty of Business and Management, 2021)
This study examines the influence of collaborative learning dimensions and social media usage on tertiary students’ engagement via e-learning mode in the time of COVID-19 pandemic situations. The dimensions of collaborative learning are interaction with peers, interaction with lecturers, and knowledge sharing; the social media or technology acceptance dimensions are mainly on the ease of use and the perceived usefulness of this new media platform. Collaborative learning and social media usage are predicted to have influenced students' learning engagement in the online and e-learning mode. 201 Malaysian tertiary students from public and private universities have completed the survey forms via purposive and snowball sampling methods. Descriptive analysis was executed in SPSS, whereas model validation and structural model were analyzed using Smart-PLS 3.3. The results revealed that collaborative learning positively influences the interaction with peers and lecturers and knowledge-sharing behavior. Technology acceptance elements positively affect social media usage. Interaction with peers, social media usage, and knowledge sharing increases tertiary student engagement in e-learning. The only insignificant predictor is interaction with lecturers. This study revealed positive findings that social media usage is the most dominant and high-performance factor impacting tertiary student engagement in e-learning.